Uso de geotecnologias na análise da biomassa florestal no estado da Paraíba - Coelho, Ivan de Almeida Machado (2016)
The mankind had the idea of a nature as an infinite source of resources, causing a transformation in the nature, providing high levels of degradation with the reduction of the biodiversity by anthropic actions. The vegetal cover of the Paraíba state, mostly, it is highly anthropic as a consequence of the opening to agricultural exploitation and mainly by the timber exploitation as energy source, where this changes make significant impacts in the quality of the stated environment. The geoprocessing is considered one of the most important instruments to understand the structures and the dynamics of vegetal cover in many space and time scales, when used in landscape ecology gives information for the study of relations between humans and environment and to understand ecologic processes. This work has as objective show the role of the non-supervised digital images process techniques for multi-time environment degradation analysis in the state of Paraíba. The area of study of this work it was the state of Paraíba, in the mesoregions of Sertão Paraibano, Borborema and Agreste Paraibano. The rains are bad distributed during the year, with diversified climatic situations, associated to distribution of the weather with the localization, observing in the regions near of the coast the weather is wetter, and how far from coast, drier is the weather. The methodology is based in the multi-time analysis of the orbital images from TM/Landast-5 satellite for the dates in the months September, 1998 and September, 2009, for the mesoregion of Sertão Paraibano, October, 1999 and September, 2008, for the mesoregion Borborema, and April, 1999 and July, 2007, for the mesoregion of Agreste Paraibano, where the images used in this work it was obtained from Instituto Nacional de Pesquisas Espaciais (INPE). The results indicate that the temperature and precipitation are straightly associated with the quantitative of vegetal cover, and it can be notified in all mesoregions, observed from the vegetal cover classes, where the increase of the thin vegetation is shown very worrying, due it is in this class that the degradation levels may increases starting the desertification cores. The work shown the great potential of the using of geoprocessing tools for a space analysis of the studied area, and from this point do a study about the dynamics of the vegetal cover of the studied area.